The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/9369047
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model of Coating Growth Rate for Varied Dip-Angle Spraying Based on Gaussian Sum Model

Abstract: In automatic spraying of spray painting robot, in order to solve the problems of coating growth rate modeling for varied dip-angle spraying technology, a prediction mode of coating growth rate using the Gaussian sum model is proposed. Based on the Gaussian sum model, a theoretical model for coating growth rate with varied dip-angle spraying is established by using the theory of differential geometry. The coating thickness of the sample points in the distribution range of the coating was obtained by making the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The rate of deposition of the spray liquid on a surface perpendicular to the direction of the spray at a distance can be modeled as a Gaussian distribution with a standard deviation and zero mean. [27] , [28] , [34] , [96] The deposition rate at the center of the circular cross-section is . The parameters , , and can be determined experimentally.…”
Section: The Disinfectant Spray Modelmentioning
confidence: 99%
“…The rate of deposition of the spray liquid on a surface perpendicular to the direction of the spray at a distance can be modeled as a Gaussian distribution with a standard deviation and zero mean. [27] , [28] , [34] , [96] The deposition rate at the center of the circular cross-section is . The parameters , , and can be determined experimentally.…”
Section: The Disinfectant Spray Modelmentioning
confidence: 99%
“…The static spraying model of the spray gun is the basis of the spray trajectory optimization. At present, β distribution model, elliptical double-β distribution model and Gaussian sum model [14]- [17] and other mathematical model are mainly used to describe coating deposition distribution for various types of spray gun after static spraying, but these models consider fewer controllable parameters of the spray gun, the existing problem can no longer meet the current needs of multi-variable spraying of complex surface.…”
Section: Static Spray Model Of Spray Gun With Variable Posturementioning
confidence: 99%
“…The microscopic mechanism of spray film thickness build-up was investigated, 5 and the distribution pattern of film thickness and the causes of film formation were explained at the microscopic level by combining a multi-field coupled flow field theory model with a film thickness distribution model. Zeng et al 6 and Liu 7 conducted a series of spraying experiments with a spray gun under tilted conditions and established a coating thickness distribution model based on the Gaussian sum model with variable tilt angle. The experiments showed that the Gaussian sum model 8 also has high fitting accuracy in describing the coating growth rate for spraying at different inclination angles.…”
Section: Introductionmentioning
confidence: 99%